Use of dietary supplements in Olympic athletes is decreasing: a follow-up study between 2002 and 2009 - Heikkinen, A.; Alaranta, A.; Helenius, I.; Vasankari, T. (Journal of the International Society of Sports Nutrition, 2011)
The aim of this study was to assess the frequency of use of dietary supplements (DS) among large sample of elite Finnish athletes and to describe possible changes in dietary supplement use between the years 2002 and 2009. Methods: A prospective follow-up study was conducted in Olympic athletes. The first survey was conducted on Olympic athletes in 2002 (N=446) and the follow- up study was conducted between May 2008 and June 2009 (N=372). Results: In 2002, a total of 81% of the athletes used dietary supplements (a mean of 3.37 +/- 3.06 DS per user) and in 2009, a total of 73% of the athletes (a mean of 2.60 +/- 2.69 per DS user) used them. After adjusting for age-, sex- and sport type, the OR (95% confidence interval, CI) for use of any dietary supplement was significantly less in 2009 as compared with 2002 results (OR, 0.62; 95% CI, 0.43-0.90). Decrease in DS use was observed in all supplement subgroups (vitamins, minerals, nutritional supplements). Athletes in speed and power events and endurance events reported use of any dietary supplement significantly more often than team sport athletes both in 2002 and 2009. In year 2009, the frequency of all dietary supplement use increased when athlete's age increased and the increase was significant in older age groups: of the athletes under 21 years 63%, 21-24 years 83% and over 24 years 90% consumed nutritional supplements. Conclusions: Based in our study, there seems to be a lowering trend of dietary supplement use among elite Finnish athletes although differences between sport subgroups and age groups are considerable.